2015
DOI: 10.1039/c5ee02328a
|View full text |Cite
|
Sign up to set email alerts
|

A circular membrane for nano thin film micro solid oxide fuel cells with enhanced mechanical stability

Abstract: Solid oxide fuel cells (SOFCs) utilizing nanoscale thin film technology has effectively decreased their operating temperatures from typically required to be in the 800°C to 1000°C range to below 500°C. By the help of silicon micromachining technology, such nanoscale thin film electrolytes were fabricated as a free-standing membrane. However, in order to minimize the internal resistance of the cell, the membrane is usually made to be only a few tens of nanometers in thickness, and subsequently its mechanical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 34 publications
0
32
0
1
Order By: Relevance
“…We adopted an MEA structure that was composed of Pt electrodes and yttria-stabilized zirconia (YSZ) electrolyte with thickness of 100 nm as a reference case. Based on the reference case, the effect of operating temperature and electrolyte thickness on electrochemical performance was investigated and compared with experimental data of literature [13]. Following assumptions were made in this study.…”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…We adopted an MEA structure that was composed of Pt electrodes and yttria-stabilized zirconia (YSZ) electrolyte with thickness of 100 nm as a reference case. Based on the reference case, the effect of operating temperature and electrolyte thickness on electrochemical performance was investigated and compared with experimental data of literature [13]. Following assumptions were made in this study.…”
Section: Model Descriptionmentioning
confidence: 99%
“…All of the boundary and operating conditions for the present study were determined from the experimental condition of the literature [13], as shown in Table 3. At the interface of ambient air/cathode, a mass fraction (O 2 :N 2 :H 2 O = 0.228:0.749:0.023) and electric potential (0.2~1.0 V) were applied as boundary conditions.…”
Section: Boundary and Operating Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have known, suitable temperature is required to bond electrode paste to electrolyte layer while to maintain enough porosity/composition integration for fast gas diffusion, facilitated electrode reaction and easy current collection, and to prevent from the undesirable reaction. The cathode fabrication temperatures (900–1100 °C) are much higher than those used in the ceria–carbonate‐based fuel cell device, except with some dedicated cell fabrication technologies, such as impregnation or vacuum cell component fabrication method . Therefore, it is believed that carbonate plays as the ‘glue’ to conglutinate the electrode and electrolyte, which ensures a low annealing temperature, while gives a well‐bonded interface for faster charge transportation (Figure b and c).…”
Section: Role Of Carbonatementioning
confidence: 99%
“…Moreover, most of the self-supported membranes on silicon are square shaped due to the anisotropic wet etching of the substrate 7 . However, it has been demonstrated that circular shape provides enhanced mechanical stability to the membrane avoiding stresses created on the corners 14 . Thanks to the doped-silicon slabs the shape of the membrane is defined by the lithography step rather than the wet etching and circular membranes can be achieved.…”
Section: Micro Sofc Conceptmentioning
confidence: 99%